2012
DOI: 10.4162/nrp.2012.6.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vegetarians have low oxidative stress, body fat, and cholesterol levels

Abstract: Excessive oxidative stress and abnormal blood lipids may cause chronic diseases. This risk can be reduced by consuming an antioxidant- and fiber-rich vegetarian diet. We compared biomarkers of oxidative stress, antioxidant capacity, and lipid profiles of sex- and age-matched long-term vegetarians and omnivores in Korea. Forty-five vegetarians (23 men and 22 women; mean age, 49.5 ± 5.3 years), who had maintained a vegetarian diet for a minimum of 15 years, and 30 omnivores (15 men and 15 women; mean age, 48.9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 35 publications
2
42
0
10
Order By: Relevance
“…Pengukuran tinggi badan menggunakan microtoise dengan ketelitian 0,1 cm, dan pengukuran berat badan dengan menggunakan timbangan injak digital dengan ketelitian 0,1 kg. Hasil ukur IMT dikategorikan menjadi underweight (<18,5 kg/m 2 ), normal (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)9 kg/m 2 ), overweight (23,0-24,9 kg/m 2 ), obesitas I (25,0-30,0 kg/m 2 ).…”
Section: Bahan Dan Metodeunclassified
See 3 more Smart Citations
“…Pengukuran tinggi badan menggunakan microtoise dengan ketelitian 0,1 cm, dan pengukuran berat badan dengan menggunakan timbangan injak digital dengan ketelitian 0,1 kg. Hasil ukur IMT dikategorikan menjadi underweight (<18,5 kg/m 2 ), normal (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)9 kg/m 2 ), overweight (23,0-24,9 kg/m 2 ), obesitas I (25,0-30,0 kg/m 2 ).…”
Section: Bahan Dan Metodeunclassified
“…Hal ini sejalan dengan penelitian di Korea yang melaporkan bahwa terdapat perbedaan asupan asam lemak jenuh antara kedua kelompok (p=0,000). 8 Terdapat 8 vegetarian dan 21 nonvegetarian yang memiliki asupan asam lemak jenuh yang tergolong berlebih. Perbedaan asupan lemak dan asam lemak jenuh antara kedua kelompok dikarenakan tidak dikonsumsinya daging oleh kelompok vegetarian.…”
Section: Perbedaan Asupan Zat Gizi Antara Wanita Vegetarian Dan Nonveunclassified
See 2 more Smart Citations
“…These catechins have strong antioxidant properties and free radical scavenging activity, antimicrobial and antiviral agent [25] [26]. Many studies have shown that green and black teas have anticholesterolemic effect [27] [28] modulation of plasma lipid profiles [29] and enhancing vasodilatation [30], increasing fatty acid oxidation and insulin sensitivity. Pears (Pyruscommunis) gained popularity among consumers due to its good taste and high digestibility.…”
Section: Introductionmentioning
confidence: 99%